Study on the serum level of CoQ10B in patients with Moyamoya disease and its mechanism of affecting disease progression - Jian MA; Xudong FU; Shaolong ZHOU; Enping MENG; Zhuo YANG; Hengwei ZHANG (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: At present, the etiology and pathogenesis of Moyamoya disease (MMD) are not completely clear. Patients are usually diagnosed after cerebrovascular events. Therefore, it is of great clinical significance to explore the predictive factors of MMD. Objective: This study aimed to investigate the serum level of CoQ10B, the amount of endothelial progenitor cells (EPCs), and mitochondrial function of EPCs in MMD patients. Methods: Forty-one MMD patients and 20 healthy controls were recruited in this study. Patients with MMD were divided into two groups: Ischemic type (n=23) and hemorrhagic type (n=18). Blood samples were collected from the antecubital vein and analyzed by CoQ10B ELISA and flow cytometry. Measures of mitochondrial function of EPCs include oxygen consumption rate (OCR), mitochondrial membrane potential, Ca2+ concentration, adenosine triphosphatases activity and ROS level. Results: The serum CoQ10B level in MMD patients was significantly lower than that in healthy controls (p<0.001). The relative number of EPCs in MMD patients was significantly higher than that in healthy controls (p<0.001). Moreover, the OCR, mitochondrial membrane potential and ATPase activity were decreased and the Ca2+ and reactive oxygen species levels were increased in MMD patients (p<0.001). Conclusions: Our results showed obviously decreased serum CoQ10B level and increased EPCs number in patients with MMD compared with healthy patients, and the mitochondria function of EPCs in MMD patients was abnormal.